2022
DOI: 10.1002/hsr2.964
|View full text |Cite
|
Sign up to set email alerts
|

Changes in emotion regulation skills of school age children from the eyes of healthcare workers during the COVID‐19 pandemic in Turkey: A cross‐sectional study

Abstract: Background and Aims While health workers were affected by the COVID‐19 pandemic on an individual and professional basis, their families and especially their children were directly or indirectly exposed to similar factors. This study aims to compare the emotion regulation competencies of school‐age children of healthcare workers in Turkey, before and during the COVID‐19 pandemic and to investigate their emotion regulation competencies during the pandemic in terms of care conditions, daily life activities and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Research findings have been mixed and some studies have suggested that children of HCWs may experience positive outcomes as well [ 34 ]. Similarly, the current study found that competence scores were significantly higher in children of HCWMs, suggesting young children of HCWMs may have experienced positive outcomes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Research findings have been mixed and some studies have suggested that children of HCWs may experience positive outcomes as well [ 34 ]. Similarly, the current study found that competence scores were significantly higher in children of HCWMs, suggesting young children of HCWMs may have experienced positive outcomes as well.…”
Section: Discussionmentioning
confidence: 99%